Characterization of Leaf Rust Resistance in International Barley Germplasm Using Genome-Wide Association Studies - A. Ziems, Laura; Singh, Lovepreet; Dracatos, Peter M; J. Dieters, Mark; Sanchez-Garcia, Miguel; Amri, Ahmed; Verma, Ramesh Pal Singh; Park, Robert; Singh, Davinder (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
A panel of 114 genetically diverse barley lines were assessed in the greenhouse and field for resistance to the pathogen Puccinia hordei, the causal agent of barley leaf rust. Multi-pathotype tests revealed that 16.6% of the lines carried the all-stage resistance (ASR) gene Rph3, followed by Rph2 (4.4%), Rph1 (1.7%), Rph12 (1.7%) or Rph19 (1.7%). Five lines (4.4%) were postulated to carry the gene combinations Rph2+9.am, Rph2+19 and Rph8+19. Three lines (2.6%) were postulated to carry Rph15 based on seedling rust tests and genotyping with a marker linked closely to this gene. Based on greenhouse seedling tests and adult-plant field tests, 84 genotypes (73.7%) were identified as carrying APR, and genotyping with molecular markers linked closely to three known APR genes (Rph20, Rph23 and Rph24) revealed that 48 of the 84 genotypes (57.1%) likely carry novel (uncharacterized) sources of APR. Seven lines were found to carry known APR gene combinations (Rph20+Rph23, Rph23+Rph24 and Rph20+Rph24), and these lines had higher levels of field resistance compared to those carrying each of these three APR genes singly. GWAS identified 12 putative QTLs; strongly associated markers located on chromosomes 1H, 2H, 3H, 5H and 7H. Of these, the QTL on chromosome 7H had the largest effect on resistance response to P. hordei. Overall, these studies detected several potentially novel genomic regions associated with resistance. The findings provide useful information for breeders to support the utilization of these sources of resistance to diversify resistance to leaf rust in barley and increase resistance durability.